The Effect of Midwives 'Assistance in Giving Solid Foods Containing Prebiotics on the Frequency of Digestive Disorders in Infants - Munawaroh; Ainal Mardiah; Kalasta Ayunda Putri; Ihda Mauliyah (CV. Get Press Indonesia, 2026)
Digestive disorders such as diarrhea, constipation, and colic are common among infants aged 6–12 months, particularly during the introduction of complementary feeding (MPASI). These conditions are often associated with inappropriate food choices and feeding practices. Complementary foods containing prebiotics may help maintain gut microbiota balance and reduce the occurrence of digestive problems. However, proper implementation of prebiotic-based complementary feeding requires guidance from health professionals, especially midwives. This study aimed to analyze the influence of midwives on the provision of prebiotic-containing complementary foods and its effect on the frequency of digestive disorders in infants. A quasi-experimental study with a pretest-posttest control group design was conducted in the working area of Ibuh Health Center, Payakumbuh City, in 2025. The sample consisted of 60 mothers with infants aged 6–12 months selected through purposive sampling and divided into intervention and control groups. The intervention group received midwife assistance regarding the provision of prebiotic-containing complementary foods for four weeks. Data were collected using questionnaires, observation sheets, and logbooks recording digestive disorder frequency. Data were analyzed using univariate and bivariate methods with the chi-square test at a 95% confidence level (α=0.05). The results showed that midwife assistance significantly reduced the frequency of digestive disorders in infants (p=0.001). Therefore, midwife assistance in providing prebiotic complementary foods is effective in reducing digestive disorders among infants.